Motivation and learning strategy: Indonesian CFL university students - Fatmawati, Fatmawati (Gema Wiralodra, 2023)
Learning a foreign language has become essential, and the Chinese language, among all international languages, is growing so fast regarding the Chinese government's active promotion. Learning and teaching Chinese as a Foreign Language in Indonesia has been practiced for a relatively long time, but the CFL learner still shows a result that is not in line with expectations. This study investigates student motivational orientation and student learning strategy use among CFL University Students in Indonesia. Random sampling CFL university students (n=160) to join the study, the MSLQ was employed to measure CFL students' motivational and learning strategies. The data were analyzed with Descriptive Statistics, Pearson Correlation, and Compare Means. The finding indicates that CFL University students' motivational orientation is at a medium level (M=3.00). With Expectancy (M=3.83, SD=.515), Value (M=3.72, SD=.522), and affective (M=3.27, SD=.579), with a motivational and learning strategy on CFL University students have a strong positive correlation and students with different motivational orientation adapt to different learning strategy. The implication of this study will give significance to the sustainability of CFL teaching and CFL learning.